Variacije na Moivreovo temo - Cedilnik, Anton (Obzornik za matematiko in fiziko, 2022)
Wegeneralize Moivre’s formula for exponentiating complex numbers, well known from high school, to all variants of two-dimensional unital algebras over any field.
Keywords: dvorazsežne enotske algebre; Moivreova formula